Good Corporate Governance, Ukuran Perusahaan, dan Sustainability Report dengan Kepemilikan Institusional Sebagai Pemoderasi - Dewi, Ida Ayu Sintya Puspita; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
This study aims to obtain empirical evidence regarding the influence of the board of directors, independent commissioners, audit committee, and company size on the sustainability report with institutional ownership as a moderating variable. The number of samples used was 117, with the sample collection method using purposive sampling method, while the data collection method used in this study was documentation. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that the board of directors, independent commissioners, and audit committee had a positive effect on the sustainability report, while company size had no effect on the sustainability report. In addition, institutional ownership is able to moderate the influence of the board of directors, independent commissioners, and company size on the sustainability report. Meanwhile, institutional ownership was not able to moderate the effect of the audit committee on the sustainability report. Keywords: Good Corporate Governance; Sustainability Report.